2007
DOI: 10.1080/10790268.2007.11753964
|View full text |Cite
|
Sign up to set email alerts
|

Lapbelt Injuries and the Seatbelt Syndrome in Pediatric Spinal Cord Injury

Abstract: Background/Objective: Approximately 250,000 patients are presently living with spinal cord injury (SCI) in the United States. Approximately 20% of patients with SCI are less than 20 years old, and 15% are less than 15 years old. The most common cause of pediatric SCI is a motor vehicle collision (MVC; ;40%); lapbelt injuries and the seatbelt syndrome are seen more often in children involved in MVCs.Methods: A search and analysis of current literature on lapbelt injuries, seatbelt syndrome, and pediatric SCI us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 9 publications
0
35
0
2
Order By: Relevance
“…To replicate glutamate excitoxicity, spinal injury has been also produced by the stable glutamate analog kainate (Magnuson et al 1999), which is not transported by membrane carriers and is often used as a paradigmatic agent to lesion brain neurons (Ben Ari and Cossart 2000). Our lab has recently shown that kainate excitotoxicity can be observed also with an isolated preparation of the neonatal rat spinal cord (Taccola et al 2008), a useful model to investigate the basic mechanisms of spinal injury with special relevance to pediatric injuries that are rather common among child trauma cases (Vitale et al 2006;Achildi et al 2007). …”
Section: Introductionmentioning
confidence: 98%
“…To replicate glutamate excitoxicity, spinal injury has been also produced by the stable glutamate analog kainate (Magnuson et al 1999), which is not transported by membrane carriers and is often used as a paradigmatic agent to lesion brain neurons (Ben Ari and Cossart 2000). Our lab has recently shown that kainate excitotoxicity can be observed also with an isolated preparation of the neonatal rat spinal cord (Taccola et al 2008), a useful model to investigate the basic mechanisms of spinal injury with special relevance to pediatric injuries that are rather common among child trauma cases (Vitale et al 2006;Achildi et al 2007). …”
Section: Introductionmentioning
confidence: 98%
“…On physical examination, a seatbelt sign was noted cephalad to his umbilicus with extension to the left flank. This pattern of injury was consistent with the use of a three-point adult lap and shoulder belt [1]. He had bilateral lower rib tenderness and midline thoracic spine tenderness upon palpation.…”
Section: Case Reportmentioning
confidence: 54%
“…The spectrum of injuries that comprises the seat belt syndrome includes fracture dislocations of the lumbar spine (chance fractures), mesenteric tears, hollow visceral blow-outs, and injury to solid intra-abdominal organs. 2,3,5,7,12 The risk of abdominal injury in the presence of SBS has been reported to be as high as 232 times more likely than in children without SBS. 9 The mechanism by which seatbelts may cause abdominal injury has been described by Abrogast et al We cite belt loading directly over the injured organ as the most common mechanism of injury.…”
Section: Discussionmentioning
confidence: 98%
“…1 The SBS has been well defined as an area of ecchymoses, erythema, or abrasions sustained secondary to seat belt use. [2][3][4][5][6][7][8] It has been reported that SBS is associated with a high risk for intra-abdominal injury. 6,9 However, other authors have reported no difference in the prevalence of abdominal injuries between belted and unbelted patients involved in a motor vehicle crash (MVC).…”
mentioning
confidence: 99%